Analysis of the Effectiveness of Social Assistance Policies in Reducing Social Inequality in Indonesia - Aulora Cinthia; Elsa Elsa; Elsae Elsae; Rea Adventia Wineini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Social inequality is one of the main challenges in development in Indonesia, reflected not only in differences in income levels but also in unequal access to economic resources, education, health, and opportunities for social mobility. In an effort to address this problem, the government has developed various social protection policies, one of which is through social assistance programs aimed at supporting poor and vulnerable groups. This study aims to analyze the effectiveness of social assistance policies in reducing social inequality in Indonesia from a public policy analysis perspective. This study uses a qualitative approach with a library research method sourced from academic books, scientific journal articles, government policy reports, and various official documents relevant to social assistance policies in Indonesia. Data analysis techniques are carried out descriptively and analytically by examining the relationship between policy design, program implementation, and their impact on reducing social inequality. The results show that social assistance policies have an important contribution in strengthening the economic resilience of the poor, maintaining minimum household consumption levels, and increasing access to basic needs. However, the effectiveness of these policies is still influenced by various factors, such as the accuracy of beneficiary targeting, institutional capacity in program implementation, the quality of governance, and the integration of policies with community economic empowerment programs. Therefore, strengthening socioeconomic data systems, improving institutional coordination, utilizing information technology, and implementing evidence-based policy approaches are crucial steps to increase the effectiveness of social assistance policies as instruments for reducing social inequality in Indonesia.